Individual Investor and Volatility: Case Robinhood - Valkama, Ville Johannes Kalervo (My University, 2024)
This thesis explores the relationship between stock price volatility and individual investor ownership, specifically focusing on the users of the Robinhood app. Individual investors play an increasingly more important role in the financial markets. Previous research connects individual investors to volatility, primarily through noise trading, herding and deviations from the decision-making processes expected by the rational choice theory. Studies on volatility involving individual investors have predominantly centred on analysing retail trading. The methodology consisted of non-parametric methods and linear regressions. We utilised the Robintrack dataset, which contains popularity metric data collected from the Robinhood brokerage, to study a sample of 3765 ordinary stocks. We first examined the contemporaneous relationship between individual investors and volatility. We sought to determine whether individual investors are associated with more volatile stocks. Based on the literature, we expected that individual investors may be associated with more volatile stocks; however, some risk-averse individual investors may systematically select lower-volatility stocks. Then, we examined whether individual investors are attracted to volatility and whether individual investor interest causes volatility. Results indicate that individual investors are associated with more volatile stocks, even after controlling for company size. The positive relationship between volatility and individual investor holdings is consistent with the two stories. First, securities that exhibit higher volatilities may attract individual investors. Second, higher volatility may result from an increase in individual investor interest. Yksityissijoittajien merkitys osakemarkkinoilla on kasvanut viime vuosina. Tutkielmassa perehdytään osakekurssien volatiliteetin ja yksityissijoittajien omistuksen väliseen suhteeseen. Aikaisempi tutkimus on yhdistänyt yksityissijoittajat ja volatiliteetin laumakäyttäytymiseen, ei-informoitujen sijoittajien mukanaoloon (ns. noise trading) ja rationaalisista malleista poikkeaviin käyttäytymistapoihin. Yksityissijoittajiin liittyvissä volatiliteettia koskevissa tutkimuksissa on pääasiassa keskitytty aktiivisen kaupankäynnin tutkimiseen. Tutkielmassa käytettiin ei-parametrisia testejä sekä lineaarisia regressioita datan analysointiin. Tutkimusaineistona hyödynnettiin Robintrack-aineistoa. Aineisto sisältää Robinhood-välittäjältä kerättyä tilastoa, joka mittaa osakkeiden suosiota käyttäjien keskuudessa. Tutkielmassa keskityttiin tavallisiin osakkeisiin, joita otoksessa oli 3765. Kirjallisuudessa esitetään, että yksityissijoittajat saattavat olla kiinnostuneempia suuremman volatiiliteetin osakkeista. Toisaalta kirjallisuuden mukaan yksityissijoittajat ovat riskejä karttelevia, he saattavat systemaattisesti valita pienemmän volatileetin osakkeita. Ensiksi tutkielmassa tarkasteltiin yksittäissijoittajien omistuksen ja osakkeiden volatiliteetin samanaikaista riippuvuutta. Tavoitteena oli selvittää, onko yksityissijoittajilla yhteys suuremman volatileetin osakkeisiin. Toiseksi selvitettiin ovatko suuremman volatileetin osakkeet houkuttelevampia yksittäissijoittajille sekä seuraako yksityissijoittajien lisääntyneestä kiinnostuksesta osakkeisiin volatiliteetin kasvua. Tulosten perusteella yksityissijoittajien omistamien osakkeiden ja niiden suuremman volatiliteetin välillä on yhteys. Suuremman volatiliteetin osakkeet näyttävät olevan houkuttelevampia yksityissijoittajille ja suurempi volatiliteetti voi johtua yksityissijoittajien kiinnostuksen lisääntymisestä
Keywords: investors; volatility (societal properties); investments (economics); fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance